Using Photovoice to stimulate critical thinking: An exploratory study with Nursing students - Elena Andina-Díaz (Universidade de São Paulo, 2020)
Objective: to explore the potentialities of the Photovoice methodology to stimulate critical thinking on Social Determinants of Health. Method: an exploratory and descriptive study with a qualitative approach, using different steps of the Photovoice methodology. Nursing students obtained photographs in their community, showing Social Determinants of Health, analyzed and classified the photographs, and exposed the results in the Nursing school. The students answered a questionnaire writing their perceptions. The data collected from the questionnaires were qualitatively analyzed. Results: 91 students participated in the study. Two main categories emerged from the data: Photovoice is a good methodology to stimulate critical thinking on Social Determinants of Health, and Photovoice is a good methodology to stimulate other skills (expressing beliefs and perceptions, stimulating creativity, developing research skills, strengthening ties with colleagues, and attracting attention). Conclusion: we explore the potentialities of the Photovoice methodology. It can be an original, simple and economical tool to stimulate critical thinking on Social Determinants of Health, and to stimulate other skills. Photovoice can be considered in teaching about aspects related to health/care in Nursing students, in order to promote critical thinking of future agents for a change in health.